STAGING CONCERNS AND APPROACHES IN EURIPIDES’ ALCESTIS: THEATRE OF VIVI - Papadopoulos, Simos; Basoucou, Lina (ΠΑΡΑΒΑΣΙΣ/PARABASIS, 2025)
This study examines the stage performance of Euripides’ Alcestis by the Theatre of Vivi, directed by Tilemachos Moudatsakis. It was presented in Greece, specifically in the villages of Crete, and was part of the alternative «off» section of the Avignon Festival in 2011. The study begins by referring to key perspectives on the genre classification of the play, mentioning the unconventional dramaturgical choices that oppose the rigid conventions typically found in the dramas of classical Athens. Following this, through an exploration and interpretive analysis of the stage codes, the study highlights the distinctive features of the performance and analyses the main points of the stage approach in relation to both the play’s genre-specific peculiarities and the broader textual context. Finally, a brief evaluation of the performance’s outcome is provided.